Estudo efeito de marcadores biológicos na atividade hemaglutinante específica e na estrutura secundária da lectina de Canavalia brasiliensis mart. ex benth - Oliveira, Aline de Carvalho (2013)
ConBr is a tetrameric protein found in Canavalia brasiliensis seeds and has affinity for D-mannose and D-glucose carbohydrates. It is vast use of this lectin in biotechnological assays due their biological properties, and it’s used commonly linked to FITC, a fluorophore widely used in various fields of biotechnology to attach to proteins a fluorescent marker through amine grouping. However, the fluorophore influence in proteins activity must be further highlighted. This research aimed obtain informations about native ConBr secondary structure and FITC-conjugated changes and start a study of this lectin conjugated quantum dots also. Samples of native ConBr, ConBr-FITC conjugated (FITC-ConBr (2%)), ConBr mixed with the FITC proportion of 2% by mass (ConBr/FITC (2%)), ConBr mixed with FITC at 20 mass% (ConBr/FITC (20%)) and processed but not conjugated with FITC ConBr (ConBr-) were analyzed by Fourier Transform Infrared spectroscopy (FTIR), mode ATR (Attenuated Total Refectance). The native ConBr, ConBr-FITC (2%), ConBr/FITC (2%), ConBr-, and conjugated quantum dots ConBr (QD ConBr-Zn / Cd) specific haemagglutinating activity were performed. The specific haemagglutinating activity in the extracts was determined using the rabbit erythrocytes suspensions at 3% in microtiter plates. The specific activity data were tested using the Mann-Whitney test. When the native ConBr and FITC-ConBr (2%) spectra were compared, it was found the peak of the native lectin relating to β- sheet structures not suffered modification when the protein was conjugated with FITC, but there was a intensity reduction in the spectrum region relating to α-helix structures, which allows a reduction in the amount these structures. There was an intensity increase of irregular structures also. Native ConBr, ConBr- e ConBr/FITC (2%) spectra suggested no changes in secondary structure. There was a ConBr-FITC (2%) hemagglutinating activity decrease and that result showed statistically significant difference to native ConBr. Native ConBr and ConBr- do not have significantly differences. The ConBr/FITC (2%) activity didn’t showed statistical differences regarding native ConBr. These results contribute and reinforce the proposition that is the FITC binding to protein promotes the structural change in the α-helix region. The ConBr-QD Zn/Cd specific activity decreased compared with the activity of native ConBr, demonstrating statistically significant differences between these samples. Statistical analyzes using the data obtained in the specific activity test and infrared spectra analysis suggest lectin ConBr FITC-conjugated secondary structure changes. However, it’s still necessary elucidate the nature of this change, and whether this is really due to the protein-fluorophore binding.